Spinal Perineural Cysts among European Patients - Kozłowski, Piotr; Kalinowski, Paweł; Kozłowska, Magdalena; Jankiewicz, Małgorzata; Budny, Agnieszka; Starosławska, Elżbieta; Burdan, Franciszek (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background A perineural (Tarlov) cyst is a fluid-filled lesion occurring between the perineurium and the endoneurium of spinal nerve roots. The aim of the study was to evaluate the prevalence and morphology of perineural cysts, detected incidentally in patients with symptomatic degenerative disk disease.Materials/methods The study was based on the retrospective data gathered during magnetic resonance imaging (MRI) examinations.Results and Conclusions Out of 3,128 spinal MRI examinations, perineural cysts were detected in 286 patients (9%). The cysts were most commonly observed in the sacral region, followed by thoracic, cervical, and lumbar regions. Cysts were more common in women than in men and the average age of patients was 54.8 years. In the majority, a single cyst was found. The average longest dimension of the lesion was 11.72 mm.
Keywords: perineural cyst; Tarlov's cyst; epidemiology; back pain; incidentally detected lesions